2020
DOI: 10.1002/jhbp.735
|View full text |Cite
|
Sign up to set email alerts
|

Impact of preoperative aspirin continuation on bleeding complications during or after liver resection: Propensity score‐matched analysis

Abstract: Background: There is insufficient evidence concerning the effect of preoperative continuation of antiplatelet therapy (APT) on intraoperative and postoperative bleeding during liver resection. This study investigated the efficacy and safety of preoperative aspirin continuation on bleeding complications during or after liver resection using propensity score matching (PSM). Methods: Between 2005 and 2018, 425 patients who underwent liver resection were enrolled in this study. Patients were divided into two group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…598 Peri-operative continuation of aspirin was not significantly associated with a higher risk of severe haemorrhagic complications in patients undergoing elective hepatectomy. 599,600 Orthotopic liver transplantation Several studies have demonstrated the association between intra-operative bleeding and blood product transfusion with postoperative morbidity and mortality after OLT. [601][602][603] Intra-operative bleeding is associated with an increased likelihood of tumour recurrence following OLT for HCC, with a more pronounced effect in patients exceeding the Milan criteria.…”
Section: Liver Surgerymentioning
confidence: 99%
“…598 Peri-operative continuation of aspirin was not significantly associated with a higher risk of severe haemorrhagic complications in patients undergoing elective hepatectomy. 599,600 Orthotopic liver transplantation Several studies have demonstrated the association between intra-operative bleeding and blood product transfusion with postoperative morbidity and mortality after OLT. [601][602][603] Intra-operative bleeding is associated with an increased likelihood of tumour recurrence following OLT for HCC, with a more pronounced effect in patients exceeding the Milan criteria.…”
Section: Liver Surgerymentioning
confidence: 99%
“…All procedures were performed by, or under the guidance of one of the board‐certified surgeons of the participating institution. The “two‐surgeon technique” for open hepatectomy reportedly enables safe parenchymal resection of the liver without severe intraoperative bleeding; 20 we applied this approach to LLR 21,22 . With this technique, rapid hemostasis is possible by clearly dividing the roles (eg, liver resection would be managed by the main surgeon and hemostasis by the assistant surgeon).…”
Section: Methodsmentioning
confidence: 99%
“…The "two-surgeon technique" for open hepatectomy reportedly enables safe parenchymal resection of the liver without severe intraoperative bleeding; 20 we applied this approach to LLR. 21,22 With this technique, rapid hemostasis is possible by clearly dividing the roles (eg, liver resection would be managed by the main surgeon and hemostasis by the assistant surgeon). The indication for LLR was limited to a tumor diameter of ≤10 cm.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…Two retrospective cohort studies employing a large number of cases were reported on laparoscopic GE surgery [ 6 ] and open GE surgery [ 7 ] to provide evidence for the safety of preoperative aspirin treatment during GE operations. Preoperative aspirin monotherapy did not affect the occurrence of surgical blood loss or postoperative bleeding complications in various types of GE surgery, including pancreatic surgery [ 10 ], liver resection [ 11 , 12 ], laparoscopic cholecystectomy [ 13 ], and laparoscopic colorectal surgery [ 14 ], according to recently published studies. Furthermore, Fujikawa et al found that stopping APT before surgery was the most important risk factor for perioperative thromboembolic events and that continuing aspirin before surgery lowered the risk of thromboembolism considerably [ 2 ].…”
Section: Reviewmentioning
confidence: 99%
“…Although using a single aspirin in the perioperative phase is not linked to an increased risk of major bleeding issues [ 12 , 14 ], using several APTs or a combination of ACT and APT in surgical patients is more difficult. In a meta-analysis of large studies, dual APT with clopidogrel and aspirin was connected to a higher risk of severe bleeding [ 16 ].…”
Section: Reviewmentioning
confidence: 99%